Faktor Sosial-Demografi dan Perilaku yang Mempengaruhi Risiko Demam Berdarah Dengue di Wilayah Endemis: Tinjauan Sistematis - Selvi Yani; Anisa Alpini; Ananda Lazulfa; Yessi Harnani (CV. ITTC INDONESIA, 2026)
Dengue Hemorrhagic Fever (DHF) is an endemic disease that remains a public health challenge in tropical regions. Various studies show that socio-demographic factors and community behavior play an important role in influencing the risk of DHF transmission. This review aims to analyze these factors based on findings from international and national journals. The writing method used a literature review of 15 journal articles examining research results related to sociodemographic variables, preventive behaviors, and environmental conditions that influence the incidence of DHF. The results of the study show that population density, education level, income, age, housing conditions, and prevention practices such as 3M, water storage management, and community participation are associated with an increase or decrease in the risk of DHF. Behavioral and environmental factors have been proven to contribute significantly to the presence of larvae and the opportunity for transmission. In conclusion, efforts to control dengue fever need to consider behavior-based approaches and the sociodemographic characteristics of the local community.